2018
DOI: 10.4049/jimmunol.1701546
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the First Teleost CD5 Molecule: Additional Evidence on Phenotypical and Functional Similarities between Fish IgM+ B Cells and Mammalian B1 Cells

Abstract: Despite teleost fish being the first animal group in which all elements of adaptive immunity are present, the lack of follicular structures, as well as the fact that systemic Ab responses rely exclusively on unswitched low-affinity IgM responses, strongly suggests that fish B cell responses resemble mammalian B1 cell responses rather than those of B2 cells. In line with this hypothesis, in the current study, we have identified a homolog of CD5 in teleost fish. This pan-T marker belonging to the scavenger recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 95 publications
3
40
0
Order By: Relevance
“…In conclusion, we have demonstrated that teleost fish preferentially respond to TI antigens over TD antigens, in correlation with the many similarities found between fish IgM + B cells and mammalian B1 cells (60). Despite this, fish IgM + B cells responded to TD antigens activating the transcription of several genes related to immune processes, many of which lead to the activation of the NF-κB pathway.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In conclusion, we have demonstrated that teleost fish preferentially respond to TI antigens over TD antigens, in correlation with the many similarities found between fish IgM + B cells and mammalian B1 cells (60). Despite this, fish IgM + B cells responded to TD antigens activating the transcription of several genes related to immune processes, many of which lead to the activation of the NF-κB pathway.…”
Section: Discussionsupporting
confidence: 75%
“…In teleost fish, the fact that no cognate GCs are ever organized and there is no CSR seem to account for the low affinity maturation of antibodies during the primary and secondary immune responses observed in these species (56,57). Furthermore, a substantial amount of evidence has been gathered by different authors in recent years pointing to a phenotypic and functional resemblance between fish IgM + B cells and mammalian B1 cells (58)(59)(60)(61). In this context, under the mammalian paradigm that long-lived memory responses are only achieved through TD class-switched responses mounted within GCs, it would seem plausible to predict that teleost fish are not able to mount long-lived B cell memory responses.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, fish B cells are one main cell types implicated in the early response to inflammation ( 25 , 46 ). Furthermore, fish B cells have a similar surface IgM/IgD ratio, size, and complexity than mammalian B1 cells ( 47 ). In addition, unlike mammalian B2 cells and similar to B1 cells, fish IgM + B cells are incapable of proliferating upon BCR cross-linking ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fish B cells have a similar surface IgM/IgD ratio, size, and complexity than mammalian B1 cells ( 47 ). In addition, unlike mammalian B2 cells and similar to B1 cells, fish IgM + B cells are incapable of proliferating upon BCR cross-linking ( 47 ). In this context, it seems interesting to establish how cytokines of the TNF ligand superfamily affect fish B cells, taking into account that B2 and B1 cells seem to respond differently in mammals to these cytokines ( 35 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation